Comparison of gut transcriptome and bacterial composition of the yellow peach moth, Conogethes punctiferalis larvae associated with host plants adaptation - Gao, Yuqing; Ji, Mengqi; Li, Shaohua; Wang, Saige; Zhao, Yanfen; Xu, Yongyu; Chen, Zhenzhen; Sun, Jianghua; Kang, Zhiwei; Liu, Fanghua (CABI agriculture and bioscience, 2024)
The yellow peach moth, Conogethes punctiferalis, is one of the most destructive polyphagous pests to corn crops in the Huang-Huai-Hai summer corn region of China. However, little is known about the host plant adaptation mechanism of C. punctiferalis. In this study, we analyzed the performance of C. punctiferalis on two of its favorable host plants (corn and sorghum). Then, we used RNA-seq and 16S rRNA sequencing to explore the potential adaptation mechanism of C. punctiferalis on these two host plants. Results showed that C. punctiferalis gained more fresh weight on sorghum while its total lipid and triglyceride content was significantly lower than on corn. In total, 2155 genes weredifferentially expressed (DEGs) between corn and sorghum reared C. punctiferalis. Most of the DEGs were involved in nutritional biosynthesis and metabolism including amino acid biosynthesis, protein digestion and absorption, and glycolysis. Enzymatic analyses revealed that C. punctiferalis reared on corn had higher trypsin activity but lower P450 activity than that reared on sorghum. Meanwhile, C. punctiferalis reared on corn harbored more gut bacteria, while its diversity is lower than that reared on sorghum. The potential functional prediction of the gut bacteria revealed that nutritional metabolism functions were differently enriched between two host plants of C. punctiferalis. Taken together, these findings clarify the impact of host plants on the gene expression and gut bacteria in C. punctiferalis. They also suggest that the plasticity of gene expression and gut bacteria cooperatively contribute to insect host adaptation of insects.